Report on blocking off land along the railway line [electronic resource] : also, mineral statistics for current year - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's, Nfld. : Robinson, 1917)
Tables. Running title: Geological Survey of Newfoundland report for 1898. "For the year 1898." Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44